Teacher Readiness towards the Offer of Malaysian Skills Certificate in Special Education Integration Programme in Secondary Schools - Suhaina Suriman; Mohd Mokhtar Tahar (Journal of ICSAR, 2018)
The Malaysian Skills Certificate (SKM) is a skill certificate awarded to the students with special needs (MBK) who learn in Special Education Integration Program (PPKI) in secondary schools after 5 years of learning duration beginning the year 2017. This certification is to provide opportunities for more MBK to be recognised in terms of skills that they possess and to produce more skillful learners among MBK. Therefore, the purpose of this study is to identify the level of teacher readiness in the aspects of knowledge, skills and attitude of secondary PPKI teachers towards SKM offerings. This study is based on the Thorndike theory by modifying the Shullman PKIK Model, Katz Model and ABC Attitude Model. This descriptive and inference review study uses a five-point Likert scale questionnaire as an instrument. A total of 30 special PPKI Special Education teachers were purposely selected in the Petaling Perdana district. The data obtained were analyzed using SPSS software. The findings show that teachers’ knowledge level is high, skills are moderate, and teachers’ attitude is high. The independent T-test shows no significant difference between teachers’ level of knowledge based on gender. One-way ANOVA test shows that there is no significant difference between teachers’ skills and teaching experience and there is no difference between teachers’ attitude based on teacher’s academic qualification. The researcher hopes that the findings would help the Ministry of Education to improve the skills of the teachers by giving SKM recognition to them before conducting vocational teaching. The success of teachers in training MBK students in vocational fields can produce students who are competitive, skillful and have a career that can contribute to themselves, families, communities and the country